Coarsening of one-step deposited organolead triiodide perovskite films via Ostwald ripening for high efficiency planar-heterojunction solar cells. Issue 18 (11th April 2016) - Zhu, Weidong; Bao, Chunxiong; Wang, Yangrunqian; Li, Faming; Zhou, Xiaoxin; Yang, Jie; Lv, Bihu; Wang, Xiaoyong; Yu, Tao; Zou, Zhigang
Abstract : The remarkable grain coarsening in one-step deposited OTP films for high efficiency planar-heterojunction perovskite solar cells. Abstract : Large organolead triiodide perovskite (OTP) grains with little intragranular defects are beneficial to minimize carrier recombination, hence boosting cell performance. However, OTP films deposited by the widely used one-step spin-coating route are usually composed of small grains, because the poor thermal stability of OTP inherently restricts the processing window (temperature, time) during the film preparation, thus limiting grain coarsening in the film. Herein, the remarkable grain coarsening via Ostwald ripening in one-step deposited OTP films has been successfully realized by a facile and effective post-synthesis high-temperature heating treatment assisted with spin-coated CH3 NH3 I. By systematically investigating the heating treatment parameters, a high-quality OTP film with an enlarged average grain size from ∼280 nm to 1.2 μm, greatly enhanced crystallinity, and excellent stoichiometry is achieved. Benefiting from such improved features, this modified film shows significantly reduced defect states corresponding to the decrease of recombination centers, as well as enhanced carrier transport and injection properties, which lead to the dramatically boosted efficiency from 14.54% to 16.88% for planar-heterojunction solar cells. More importantly, the improved OTP film quality provides the possibility of thickening the absorber layer of cells to realize more sufficient absorption without serious aggravation of charge recombination. By further optimizing the thickness of the coarsened OTP films, highly efficient cells with relatively excellent reproducibility and an optimal efficiency of 19.24% are achieved.